Recién nacidos de bajo peso: de los factores de riesgo sociobiológicos maternos Hospital II IPSS – Tarapoto - 1994 - Célis Cruz, Esther (1995)
It was an analytical case-control prospective data developed in the hospital II IPSS, Tarapoto from March to November 1994, to determine the factors most important maternal risk that relate to the newborn of low weight and establish the change in the study population if the factor is controlled. 1259 births were attended with the newborn alive, 93 of them had low birth weight, at a frequency of 7.38%. Risk factors associated with low birth weight are: Neonatal: Preterm (OR = 115.12) and small for gestational age (OR = 15.86). Conceptional: Gestational age (OR 19.87), chronic anemia (5.56), pregnancy-induced hypertension (OR = 2.24) and antenatal care (OR = 4). Preconception: intergenesic period (OR = 4.15) maternal age (OR = 2.6), education (OR = 2.24) 'origin (OR = 2.2) and parity (OR = 1.98). The risk factors to be modified produce a significant decrease in underweight would RN: Preterm, small for gestational age, gestational age, chronic anemia, prenatal care, intergenesic period, maternal age, parity, education and origin.